2018
DOI: 10.1111/ced.13732
|View full text |Cite
|
Sign up to set email alerts
|

Post-bariatric surgery hidradenitis suppurativa: a new patient subset associated with malabsorption and micronutritional deficiencies

Abstract: Post-BS HS may represent a new patient subset, requiring customized clinical management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…However, a retrospective study showed that post-BS, HS patients presented with micro-nutritional deficiencies and insufficient responses to standard first-line antibiotic treatments. Zinc was found to be at significantly lower serum levels in post-BS patients with HS compared to those patients with HS who had not undergone BS 27 . A recent systematic review also found that a subset of HS patients after BS had a significant increase in panniculus and experienced HS exacerbations in the excess panniculus, requiring excision of loose skin 28 .…”
Section: Pathophysiology and Triggers Of Hsmentioning
confidence: 80%
“…However, a retrospective study showed that post-BS, HS patients presented with micro-nutritional deficiencies and insufficient responses to standard first-line antibiotic treatments. Zinc was found to be at significantly lower serum levels in post-BS patients with HS compared to those patients with HS who had not undergone BS 27 . A recent systematic review also found that a subset of HS patients after BS had a significant increase in panniculus and experienced HS exacerbations in the excess panniculus, requiring excision of loose skin 28 .…”
Section: Pathophysiology and Triggers Of Hsmentioning
confidence: 80%
“…Hidradenitis suppurativa and psoriasis can remain the same, worsen, or improve after bariatric surgery. Diabetic skin changes, such as acanthosis nigricans and necrobiosis lipoidica, can improve [ 1 , 3 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The four common types of weight loss surgery include duodenal switch with biliopancreatic diversion, laparoscopic adjustable gastric banding, Roux-en-Y gastric bypass, and sleeve gastrectomy. Bariatric surgery not only can affect the skin, but also can cause or modify cutaneous diseases [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The most specific adverse skin reactions to this intervention include bowel-associated dermatosis and arthritis syndrome, erythematous macular eruption with a neutrophilic infiltrate, non-pruritic papular eruption with IgG and C3 deposition, and erythema nodosum ( 71 , 72 ). In addition, a new subset of HS associated with malabsorption and deficiency in micronutrients has been described ( 73 ). Zinc deficiency resulting from malabsorption in bariatric surgery has been linked to the development of the rare condition known as necrotic migratory erythema ( 74 ).…”
Section: Adverse Skin Reaction To Anti-obesity Treatmentmentioning
confidence: 99%